2017
DOI: 10.21013/jems.v8.n1.p12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Working Conditions on Teacher’s Job Satisfaction and Performance in the Private Primary Schools in Yei Town, South Sudan

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…It was concluded that there is a significant relationship between these factors of motivation and the efficiency of teachers. Wahu (2017) studied the impact of working conditions of teachers' satisfaction and performance in private primary schools in Yei Town in South Sudan. The study used a survey design with simple random sampling technique to establish the relationship between the two variables.…”
Section: Relationship Between Job Satisfaction and Teachers' Performancementioning
confidence: 99%
“…It was concluded that there is a significant relationship between these factors of motivation and the efficiency of teachers. Wahu (2017) studied the impact of working conditions of teachers' satisfaction and performance in private primary schools in Yei Town in South Sudan. The study used a survey design with simple random sampling technique to establish the relationship between the two variables.…”
Section: Relationship Between Job Satisfaction and Teachers' Performancementioning
confidence: 99%
“…Seperti Shafiq (2015) menyatakan adanya pengaruh positif antara kinerja guru dengan lingkungan kerja. Begitu juga dengan penelitian yang dilakukan oleh Ohide & Mbogo (2017), Al-Omari, K., & Okasheh, H. (2017). Husnul (2017).…”
Section: Lingkungan Kerjaunclassified